Identification of Mesoscale Convective System Phenomena in Relation to Heavy Rain in Semarang (Case Study of the Squall Line on March 13, 2024) - Cahya, Shintia Dwi; Halawa, Reinal Taruna Wahyu; Alghazali, Muhammad Fathurrachman; Saifulloh, Naufaldi; Kristianto, Aries (Department of Physics – Universitas Negeri Padang UNP, 2025)
Indonesia, located in the equatorial region, experiences complex rainfall variability influenced by various climatic and geographic factors. Mesoscale Convective Systems (MCS), including squall lines, are a significant contributor to extreme weather phenomena such as heavy rainfall and strong winds. This study investigates the mesoscale convective system (MCS) phenomenon, focusing on its formation, atmospheric dynamics, and associated rainfall distribution. This research investigates the squall line phenomenon, specifically focusing on a squall line event in Semarang, Indonesia, on March 13, 2024. Utilizing data from Himawari-8 satellite imagery, ERA5 reanalysis, and GSMaP rainfall observations, the research identifies the development, atmospheric dynamics, and rainfall intensity of the squall line. Satellite imagery analysis revealed the squall line's linear pattern with cloud top temperatures below -60°C, forming during intense convective activity. Atmospheric instability indices, including CAPE and LI, indicated favorable conditions for squall line development, based on a Skew-T Log-P diagram, shows CAPE values reaching 427 J/kg, minimal CIN, and increasing wind shear with altitude. Rainfall distribution analysis identified localized extreme precipitation exceeding 120 mm within the study period, which aligns with the squall line's trajectory. The findings highlight the significant role of squall lines in triggering heavy rainfall and hydrometeorological disasters in Indonesia, emphasizing the need for accurate monitoring and early warning systems.The findings highlight the critical role of mesoscale dynamics in triggering squall lines and their potential to induce hydrometeorological disasters. This study underscores the need for improved monitoring and forecasting of MCS events to mitigate their impacts on vulnerable regions like Semarang.